Physical confinement alters sarcoma cell cycle progression and division. Issue 19 (18th October 2018) - Moriarty, Rebecca A.; Stroka, Kimberly M.
ABSTRACT: Tumor cells experience physical confinement on one or multiple axes, both in the primary tumor and at multiple stages during metastasis. Recent work has shown that confinement in a 3D spheroid alters nucleus geometry and delays cell division, and that vertical confinement impairs mitotic spindle rounding, resulting in abnormal division events. Meanwhile, the effects of bi-axial confinement on cell cycle progression has received little attention. Given the critical role of nuclear shape and mechanics in cell division, we hypothesized that bi-axial physical confinement of the cell body and nucleus would alter cell cycle progression. We used sarcoma cells stably expressing the fluorescence ubiquitination cell cycle indicator (FUCCI), along with fibronectin-coated microchannel devices, and explored the impact of bi-axial physical confinement on cell cycle progression. Our results demonstrate that bi-axial physical confinement reduces the frequency of cell division, which we found to be attributed to an arrest in the S/G2/M phase of the cell cycle, and increases the frequency of abnormal division events. Cell and nuclear morphology were both altered in confinement, with the most confining channels preventing cells from undergoing the normal increase in size from G1 to S/G2/M during cell cycle progression. Finally, our results suggest that confinement induces a mechanical memory to the cells, given our observation of lasting effects on cell division and morphology, even after cells exited confinement. Together, our results provide new insights into the possible impact of mechanical forces on primary and secondary tumor formation and growth.